Clinical effectiveness of Sahasthara remedy for relief of musculoskeletal pain: a systematic review and meta-analysis of randomized controlled trials - Sookying, Sontaya; Piromyapron, Mutita; Puttarak, Panupong; Vimolmangkang, Sornkanok; Saokaew, Surasak (Science, Engineering and Health Studies, 2021)
Sahasthara (SHT) has been used for more than thirty years for reducing pain. The remedy has been listed in the Thailand national list of essential medicines. Evidence on the clinical benefits of SHT has never been summarized and documented. Its effectiveness is still limited and unclear. This study aims to systematically review and meta-analyze the clinical effects of SHT for pain reduction. Studies were eligible if they measured pain intensity. Ninety-nine identified studies were systematically searched and two of those were included into the synthesis and analysis. Quality of articles was assessed using the Jadad scale and risk of bias tool. This study was performed and reported in line with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement. Two publications included in this meta-analysis were randomized control trials that compared the efficacy of SHT to diclofenac, a standard drug used for pain. SHT shows significant differences in pain reduction compared to diclofenac. Our findings indicated the potential of SHT as a pain reliever that is superior to diclofenac. Safety data, however, were not reported systematically, although the studies provided safety information compared to NSAIDs. Longitudinal studies on the efficacy and safety of SHT are needed.